2008
DOI: 10.1097/mpa.0b013e31815f2c2a
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hypoxia-Inducible Factor-1α, Histone Deacetylase 1, and Metastasis-Associated Protein 1 in Pancreatic Carcinoma

Abstract: These results suggest that HIF-1alpha expression may be regulated through HDAC1/MTA1, which is associated with a poor prognosis for pancreatic carcinoma and indicates that HIF-1alpha and HDAC1/MTA1 are a promising therapeutic target in pancreatic carcinoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(53 citation statements)
references
References 38 publications
1
51
1
Order By: Relevance
“…Histone hypoacetylation or HDACs overexpression has been linked to the development of prostate, breast, ovarian, colon, and gastric cancer [19]. It has been shown that HDACs are overexpressed in PDAC [20] and that this, together with HIF-1a overexpression, is associated with worsening of survival prognosis [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Histone hypoacetylation or HDACs overexpression has been linked to the development of prostate, breast, ovarian, colon, and gastric cancer [19]. It has been shown that HDACs are overexpressed in PDAC [20] and that this, together with HIF-1a overexpression, is associated with worsening of survival prognosis [21]. …”
Section: Discussionmentioning
confidence: 99%
“…In another expression profile of class I HDACs, HDAC1, HDAC2, HDAC3 and HDAC8 were positive in 17 (85%), 18 (90%), 20 (100%) and 18 (90%) of 20 pancreatic cancer cases, respectively, as observed by immunohistochemistry [48]. Further studies in PDAC have linked elevated HDAC1 and HDAC2 levels with poor tumor differentiation and overall survival [4951]. Ouaïssi, et al reported that approximately 80% of examined PDAC samples had a significant increase of HDAC7 at the RNA and protein levels [52].…”
Section: Nucleosome Remodeling Machines and Histone Modifying Enzymesmentioning
confidence: 99%
“…The exact mechanisms by which these drugs act in cancer therapy is not fully understood, but they appear to have pleiotropic anti-tumor effects including induction of differentiation, growth arrest, initiation of senescence, enhanced apoptosis, decreased angiogenesis, immunomodulatory activities, and an ability to synergize with traditional cytotoxic chemotherapies and radiation [Deroanne et al, 2002; Kim et al, 2003; Bolden et al, 2006; Minucci and Pelicci, 2006; Tomasi et al, 2006; Xu et al, 2007]. The clinical utility of agents that target HDAC enzymes is, in part, based upon the aberrant expression and/or function of HDACs in cancer initiation and progression, with overexpression of some HDACs correlating with poor prognosis in a number of tumor types including gastric, prostate, breast, pancreatic, lung, and hepatocellular cancers [Rikimaru et al, 2007; Miyake et al, 2008; Weichert et al, 2008a b c]. …”
mentioning
confidence: 99%